Pengembangan Multimedia Interaktif Berbasis Model Drill and Practice Materi Operasi Hitung Penjumlahan dan Pengurangan Bilangan Cacah Kelas IV SDN 4 Nyalian - Ni Made Nindya Cahyani; Gusti Ngurah Sastra Agustika; I Gusti Agung Ayu Wulandari (EduInovasi: Journal of Basic Educational Studies, 2024)
This research aims to describe the design, determine the feasibility of interactive multimedia based on the drill and practice model, and determine the effectiveness of interactive multimedia based on the drill and practice model. The product was tested by 1 subject matter expert, 1 instructional design expert, 1 learning media design expert, as well as research subjects with 3 students in individual trials, 12 students in small group trials, and effectiveness testing using 21 students. The research model used is the ADDIE model (Analyze, Design, Development, Implementation, Evaluation). This development research uses data collection methods by observation, interviews, questionnaires and tests. The data analysis techniques used are qualitative descriptive analysis, quantitative descriptive analysis and inferential statistics. The research results obtained were (1) Interactive multimedia design using the ADDIE development model, (2) the quality of interactive multimedia by subject matter content expert testing obtained a result of 89.58% in the good category, the instructional design expert test obtained a result of 91% in the very category. good, learning media design expert tests obtained 90% results in the very good category, individual trials obtained 87.89% results in the good category, and small group trials obtained 88.85% results in the good category, (3) effectiveness of interactive multimedia Based on the results of the t-test, tcount is 5.288 and ttable is 2.085, meaning tcount > ttable, so H0 is rejected and Ha is accepted. Thus, the results of this research show that Interactive Multimedia Based on the Drill and Practice Model is feasible and effective to apply for class IV Semester I in the material of arithmetic operations for addition and subtraction of whole numbers up to 1,000.